2019
DOI: 10.3390/ijerph16245133
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Telephone Aftercare Intervention for Obese Hispanic Children on Body Fat Percentage, Physical Fitness, and Blood Lipid Profiles

Abstract: We investigated effects of 10-month telephone aftercare intervention following primary obesity intervention on changes in body fat percentage, physical fitness, and lipid profiles in obese Hispanic children. Seventy-one obese children were randomly assigned to (1) primary intervention and 10-month telephone aftercare intervention (PITI; N = 26), (2) primary intervention only (PI; n = 25), and (3) control (CON; N = 20). Anthropometric data, physical fitness, and blood samples were obtained before (PRE) and afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“… 46 2019 RCT 118 DM 1 year Telephone HbA1c, BP, tobacco cessation, statin therapy, aspirin therapy, physical activity, exercise, LDL-C, medication adherence, BMI, diet Significantly greater medication use and diabetes care practices in telehealth group. Garza et al 36 2019 Pre-post 71 Obesity 1 year Telephone Body fat percentage, TC, TG, LDL-C, HDL-C, physical fitness 10-month aftercare telehealth intervention helped patients maintain significant reductions in LDL-C, TC, TGs, and increase in HDL-C. Gulayin et al 57 2019 RCT 357 HLD, CVD, DM 1 year Telephone, mobile application LDL-C, Framingham CVD risk score, statin therapy, mean annual primary care visits No difference in LDL-C between groups, but 41.5% higher rate of participants receiving appropriate statin dose in telehealth group. Maresca et al 50 2019 Pre-post 22 Mental health 1 year Telecounseling, telemonitoring BP, blood glucose levels, TC, TG, BMI, mental health Significant improvements in lipids and BMI that correlated with mental health in telehealth group.…”
Section: Resultsmentioning
confidence: 99%
“… 46 2019 RCT 118 DM 1 year Telephone HbA1c, BP, tobacco cessation, statin therapy, aspirin therapy, physical activity, exercise, LDL-C, medication adherence, BMI, diet Significantly greater medication use and diabetes care practices in telehealth group. Garza et al 36 2019 Pre-post 71 Obesity 1 year Telephone Body fat percentage, TC, TG, LDL-C, HDL-C, physical fitness 10-month aftercare telehealth intervention helped patients maintain significant reductions in LDL-C, TC, TGs, and increase in HDL-C. Gulayin et al 57 2019 RCT 357 HLD, CVD, DM 1 year Telephone, mobile application LDL-C, Framingham CVD risk score, statin therapy, mean annual primary care visits No difference in LDL-C between groups, but 41.5% higher rate of participants receiving appropriate statin dose in telehealth group. Maresca et al 50 2019 Pre-post 22 Mental health 1 year Telecounseling, telemonitoring BP, blood glucose levels, TC, TG, BMI, mental health Significant improvements in lipids and BMI that correlated with mental health in telehealth group.…”
Section: Resultsmentioning
confidence: 99%
“…Our findings are consistent with other EMM studies that provided real-time data. In rural Morocco, EMM (that provide a real-time data) increased treatment success and decreased the lost to follow-up among people with new smear positive pulmonary TB when compared to SAT alone [ 20 ]. Another study in South Africa, using SIMpill system (real-time data communicated with a web-based application by SMS every time the patient opens the bottle), also found that TB cure rates improved compared with the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Discrepancies were discussed between the 2 reviewers and a third party, when necessary, until a consensus was reached. The presence of available information across extraction categories is presented in Multimedia Appendix 2 [36][37][38][39][40][41][42].…”
Section: Charting the Datamentioning
confidence: 99%
“…Finally, a few (n=3, 42%) studies reported retention rates above 80%, with a few (n=2, 29%) studies reporting retention rates below 80%, including Bowen-Jallow et al [41] (54.2%) and Patrick et al [36] (63%). Although the focus of a scoping review is not on study outcomes, it is worth noting that studies that reported significant improvements to anthropometric or cardiometabolic outcomes used a hybrid approach of in-person and remote technology strategies and reported high acceptability and retention (≥80%) [38,40,42]. Although it is not clear what the most effective behavior change techniques are for Hispanic youths given the broad range of techniques used, all studies reported the use of 1 or more behavior change technique, which is a noteworthy strength [43,44].…”
Section: Feasibility-related Criteriamentioning
confidence: 99%